Fans' Perceptions of Professional Tennis Events' Social Media Presence: Interaction, Insight, and Brand Anthropomorphism. (October 2017) - Thompson, Ashleigh-Jane; Martin, Andrew J.; Gee, Sarah; Geurin, Andrea N.
This article aims to develop a better understanding of how sport fans perceive events' social media presence. An online qualitative survey was conducted with sport fans ( n = 105) of four professional tennis events (Australian Open, Roland Garros, Wimbledon, and U.S. Open). Findings suggest that fans perceive the events' usage of social media to be about three aspects: interaction, insight, and brand anthropomorphism. In addition, fan responses suggest that while Facebook is the most popular site for general social media usage, these fans consider Twitter to be their most preferred platform to follow the events. Finally, fan responses illustrate three barriers that brands need to overcome in order to successfully develop and execute their social media strategy: competition with other media, a lack of year-round incentives, and technological capabilities of the platforms, which ultimately influenced fans' motives and use.